CHRONOLOGICAL CLASSIFICATION OF URBANONYMS IN TASHKENT - Shohista Asqarovna Zoitova (Modern American Journals, 2025)
This article investigates the chronological classification of urbanonyms in the city of Tashkent, the capital of Uzbekistan. Urbanonyms—names of urban places such as streets, districts, neighborhoods, and squares—reflect not only the spatial organization of a city but also its historical, political, and cultural evolution. By classifying urbanonyms according to different historical periods, the study aims to reveal patterns of naming practices and the ideological shifts that have influenced them. The research spans from the pre-Soviet era through the Soviet period and into the era of independence, demonstrating how urbanonyms serve as linguistic markers of identity, memory, and power relations in the urban space. A special focus is given to the changes that occurred in the post-Soviet period, when many Soviet-era names were replaced or adapted to reflect national identity and cultural heritage. Through a combination of archival analysis, historical comparison, and semantic categorization, this article provides a comprehensive view of the transformation of Tashkent’s urban toponymy over time.
Keywords: Urbanonymy, toponymy, street naming, Tashkent, linguistic landscape, post-Soviet identity, chronological classification, cultural memory, onomastics, urban history.